Alternating Ontologies: Exchange and Ritual in Anganen History - Nihill, Michael (The Australian journal of anthropology, 1996)
In this article I examine the changing social and historical context of exchange and ritual amongst the Anganen of the Southern Highlands Province of Papua New Guinea, a neglected theme in Highland ethnography. I focus primarily on the history of the incorporation of one spirit cult ritual, rimbu, and its relationship to the other major spirit cult, kabit, and just how these two cults inter-relate with two major categories of exchange—the ceremonial pig kill (yasolu) and the more ‘mundane’ forms of exchange associated with such events as marriage and death. It is the structural parallels, differences and interconnections between these two exchange categories and the two ritual types which have guided much of the historical development of local social structure until colonisation. This has resulted in a substantial, though not necessarily stable, integration of ritual and exchange which has been ‘played out’ over the approximately fifteen-year periods between yasolu pig kills. I argue that it is this set of oppositions that provides the structural basis for different potentialities for male capacity. On occasion these may be so graphically distinct that they may be called differing social ontologies, different baselines for being and action. Different aspects of rimbu were adopted from around the turn of the twentieth century until colonisation some 50 years later when both kabit and rimbu were abandoned under mission pressure. However, to talk about the adoption of rimbu and the changes to Anganen social structure which it helped to produce as ‘pre-colonial’ history is misleading to the extent that much of the impetus for change was bound up in the efflorescence of trade caused by the Australian pearling industry in the Torres Strait. I call this period ‘ante-colonial’ in order to highlight the impact of the Australians and the irony that what the Australians indirectly helped create, rimbu as a central feature to Anganen social life, was destroyed with the direct colonial presence and missionisation.